Turkménistan : les femmes toujours en proie à l'insécurité. - Tarp Nurmagambetova, Mia (Global Voices en Français, 2023)
Une femme sur six a subi des violences de la part de son partenaire actuel ou ancien, selon la toute première enquête nationale sur la violence domestique en 2020
Turkmenistan
Keywords: 2023-12 December

Turkmenistán continúa siendo inseguro para las mujeres - Tarp Nurmagambetova, Mia (Global Voices en Español, 2023)
Una de cada seis mujeres ha sufrido violencia por parte de su pareja actual, o expareja, según la primera encuesta nacional de violencia doméstica realizada en 2020.
Turkmenistan
Keywords: 2023-12 December

Turkmenistan remains unsafe for women - Tarp Nurmagambetova, Mia (Global Voices, 2023)
One in every six women experienced violence from their current or former partner, according to the first-ever national survey of domestic violence in 2020.
Turkmenistan
Keywords: 2023-12 December

Interview with Eira Tansey about “A Green New Deal for Archives” - Burkely Hermann (Issues & Advocacy, 2023)
In a Green New Deal for Archives policy platform I think there’s an important role for community archives to play in documenting watersheds and local environmental problems. Community and activist archives can do this in ways that government archives likely could not or would not.
United States of America
Keywords: 2023-12 December

WMO issues new guidelines on evaluation of weather and climate extremes - World Meteorological Organization (World Meteorological Organization, 2023)
WMO has taken over responsibility for hosting the official Archive of Weather and Climate Extremes - the equivalent of the Guiness Book of records on heat, rainfall, wind, lightning and many other phenomena. It has also issued new guidelines on the evaluation of new records.
Worldwide
Keywords: 2023-12 December

Deploying OSINT in armed conflict settings: law, ethics, and the need for a new theory of harm - Ed Millett (Humanitarian Law & Policy Blog, 2023)
Explore the role of open-source information (OSINT) in 21st-century conflicts, its benefits in accountability and justice, and risks such as privacy violations. What are the legal frameworks and challenges in regulating OSINT's use by states and non-state actors in armed conflict settings?
Worldwide
Keywords: 2023-12 December

A movement is growing across Africa and diaspora demanding reparations for the impacts of slavery and colonialism - Zage, Zita (Global Voices, 2023)
"The demand for reparations is not an attempt to rewrite history or to continue the cycle of victimization. It's a call to recognize the undeniable truth and rewrite the wrongs ..."
Africa
Keywords: 2023-12 December

Traditional Knowledge Database strengthening weather forecasting and observations in the Pacific - Siosinamele Lu (Secretariat of the Pacific Regional Environment Programme, 2023)
There is a lot of data in our traditional knowledge. Our chants, songs, artefacts, and tattoos all hold data that only we can interpret and understand. However, there has been limited integration of this knowledge into our policies and decision-making processes.
Oceania
Keywords: 2023-12 December

What can Taiwan learn from Ukraine? - Noubel, Filip (Global Voices, 2023)
Can Taiwan learn from Ukraine as it faces military threats from China? Fighting disinformation, utilizing technology and establishing command systems are crucial.
Republic of China (Taiwan, not a UN member)
Keywords: 2023-10 November

Digital apartheid and the use of social media algorithms in humanitarian crises - Seerat Khan (Global Voices, 2023)
Big tech platforms extensively censor Palestinian voices, shadow banning them and their supporters, violating their rights to free speech, assembly, information access, political participation, and protection from discrimination.
Palestine (permanent observer to the UN)
Keywords: 2023-10 November

In Turkey, the state is targeting scores of journalists - Geybullayeva, Arzu (Global Voices, 2023)
Content about corruption or irregularities in due process is frequently blocked in Turkey. By some estimates, close to half of the blocked news is directly related to Erdoğan, his family, or other government officials.
Türkiye
Keywords: 2023-10 November

Meet the Archivist Whose Obsession for Detail Matches Martin Scorsese’s - Hemphill, Jim (IndieWire, 2023)
"Killers of the Flower Moon" executive producer Marianne Bower talks about her decades-long role as Martin Scorsese's researcher and archivist and what it meant for the director's newest film.
United States of America
Keywords: 2023-10 November

What To Expect from The International Criminal Court's Investigation in Israel and Palestine - Goldberg, Mark Leon (UN Dispatch, 2023)
The International Criminal Court is opening an investigation into war crimes and crimes against humanity in Israel and Palestine following the October 7 attacks and Israeli military action in Gaza. This may set into motion a process that leads to ICC indictments of Israelis and Palestinians.
Western Asia
Keywords: 2023-10 November

data.org Partners With the World Health Organization on Global Health Response - The Rockefeller Foundation (The Rockefeller Foundation, 2023)
This partnership will drive the development and deployment of digital public goods for pandemic and epidemic intelligence.
Worldwide
Keywords: 2023-10 November

Resisting the Colonial Imagination: The Role of Exhibition Design in the Decolonial Project - Lalli Hills, Adrienne; Middleton, Margaret (American Alliance of Museums, 2023)
The staff of First Americans Museum are among many museum professionals seeking to disrupt the methods of presentation still endemic among collections of Indigenous cultural materials. These models may feel nostalgic or elevated to some, but can make an thoughtful and compelling exhibition feel hostile for the descendants of people brutalized by European and American empires.
Worldwide
Keywords: 2023-10 November

Ahead of presidential elections, Russia rewrites history and promotes nationalism at schools - Daria Dergacheva (Global Voices, 2023)
New history books and classes called "Important Conversation" are prompting the new nationalist propaganda discourse across schools in Russia.
Russian Federation
Keywords: 2023-10 October

Antes de las elecciones presidenciales, Rusia reescribe la historia y promueve el nacionalismo en las escuelas. - Daria Dergacheva (Global Voices, 2023)
Libro escolar falsifica información sobre la invasión a Ucrania y los crímenes de Stalin
Russian Federation
Keywords: 2023-10 October

Canada Should Declassify Nazi War Criminal Report - Kirshner, Sheldon (Times of Israel - The Blogs, 2023)
The Trudeau government has a lot to do in explaining why numerous immigrants of questionable and troubling backgrounds were allowed into Canada after World War II.
Canada
Keywords: 2023-10 October

A Wartime Case for Information Integrity - Melissa Fleming (LinkedIn, 2023)
The fog of war is driving the spread of hate and lies online — resulting in dangerous errors with real-time, real-world consequences. The case for information integrity has rarely been more compelling, or more urgent.
Worldwide
Keywords: 2023-10 October

Birth Registration in the Developing World: Bridging the gap between policy and practice - Abu S. Shonchoy; Zaki Wahhaj (LSE International Development, 2023)
Birth registration is a fundamental human right, yet millions of children worldwide still lack this crucial documentation. Even though the United Nations Convention on the Rights of the Child emphasizes immediate registration after birth, the reality on the ground is quite different.
Worldwide
Keywords: 2023-10 October

Hamas Attacks, Israel Bombs Gaza and Misinformation Surges Online - Bellingcat Investigation Team (bellingcat, 2023)
Videos supposedly from the latest escalation of the conflict are actually years old, from the wrong country or don’t depict a warzone at all.
Western Asia
Keywords: 2023-10 October

Responsible Management and Use of Data in UN Peace Operations - Oksamytna, Kseniya (International Peace Institute, 2023)
In recent years, the UN has embarked on an ambitious project to use data more extensively and effectively to improve the safety of peacekeepers and the implementation of peace operations’ mandates.
Worldwide
Keywords: 2023-10 October

Conference - Is AI the End of Creativity—Or a New Beginning? - On Line 2023-11-28 - Zócalo Public Square (Zócalo Public Square, 2023)
Upcoming events - Is AI the End of Creativity—Or a New Beginning? | Friday, October 27, 2023 | Los Angeles In-Person | Streaming Online | Alan Turing, the father of computer science, predicted that “at some stage… we should have to expect the machines to take control.” As artificial intelligence tools like ChatGPT promise to revolutionize the way we think and work—and futurists talk of the technology as a next step in human evolution—“some stage” appears to be now.
United States of America
Keywords: 2023-10 October

Abus sexuels: les archives des diocèses, du pire au meilleur – Portail catholique suisse - Page, Maurice (cath.ch, 2023)
Pour chaque diocèse, les historiens de l’Université de Zurich ont fait un état des lieux de la tenue des archives ordinaires et des archives secrètes. Le bilan est mitigé entre très bon et médiocre. Mais tous ont manifesté une volonté explicite de collaboration.
Switzerland
Keywords: 2023-09 September

Comment l’Église en Suisse a failli dans la gestion des abus sexuels – Portail catholique suisse - Page, Maurice (cath.ch, 2023)
Le rapport du projet pilote sur l’histoire des abus sexuels dans l’Église suisse a permis de dénombrer, entre 1950 et 2022, 1’002 cas d’abus sexuels sur 921 victimes pour 510 auteurs. Selon les historiens, il ne pourrait s’agir là que de la partie émergée de l’iceberg. La faillite de l’institution et les négligences des évêques dans la gestion des abus sont pointées du doigt.
Switzerland
Keywords: 2023-09 September

Malaysian government told to stop playing ‘Big Brother’ to media - Palatino, Mong (Global Voices, 2023)
What is more worrying is the fact that much of the so-called 'offending' content is mere reports and opinion pieces deemed critical of the government.
Malaysia
Keywords: 2023-09 September

How Kurdish language divisions hinder access to information - Aziz, Tara (Global Voices, 2023)
The ongoing disputes among Kurdish languages and their lack of standardization create obstacles to accessing online information, impedes the flow of information, and curtails active participation in the digital realm.
Iraq
Keywords: 2023-09 September

Building the South-South Feminist Archive: An Interview with Ghiwa Sayegh of Kohl Journal - Machirori, Fungai (African Arguments, 2023)
Building the South-South Feminist Archive: An Interview with Ghiwa Sayegh of Kohl Journal
Africa
Keywords: 2023-09 September

Advice from Archives for Black Lives - Brumfield, Sara (FromThePage Blog, 2023)
How do you handle racist language in your archives? This is, unfortunately, a perennial issue. The Archives for Black Lives group in 2019 published Anti-Racist Description Resources. While you should read the whole thing (especially if you have materials pertaining to slavery), the blog author pulled out some practical bits.
Worldwide
Keywords: 2023-09 September

More than a “Slap in the Face”: ICA’s Congress in Abu Dhabi Whitewashes the UAE’s Reality - Hermann, Burkely (Issues & Advocacy, 2023)
Recently, there has been a uproar on social media about the location of The International Federation of Library Associations and Institutions (IFLA)’s World Library and Information Congress (WLIC) in 2024. Set to occur in Dubai. What is not talked about as much is the congress/conference of the International Council on Archives (ICA) in Abu Dhabi, the UAE capital, set for October 9 to October 13.
Worldwide
Keywords: 2023-09 September; Abu Dhabi Congress; ICA

Guidance Note on Data Responsibility and Accountability to Affected People in Humanitarian Action - The Centre for Humanitarian Data (The Centre for Humanitarian Data, 2023)
Data responsibility is the safe, ethical, and effective management of personal and non-personal data for operational response and is therefore central to the humanitarian system’s Accountability to Affected People (AAP).
Worldwide
Keywords: 2023-08 August

Conference - Does Confronting Our History Build a Better Future? - On Line 2023-10-27 - Zócalo Public Square (Zócalo Public Square, 2023)
Upcoming Events - How Should Societies Remember Their Sins? | Friday, October 27, 2023 | Los Angeles In-Person | Streaming Online | Attempts to confront difficult history appear to be dividing the United States and entangling communities in cultural and legal conflict. But historians, social justice activists, and many others argue that grappling with the sins of the past, and the way they reverberate into the present, is a necessary foundation for reimagining the future. What are the best and most creative ways societies are using history to make a better tomorrow?
United States of America
Keywords: 2023-08 August

Conference Call for Proposals - ARL IDEAL 2024—Inclusion, Diversity, Equity, and Accessibility in Libraries & Archives Conference - 2024-07-15 to 17, in Toronto, Canada - Keig, Alisha (Association of Research Libraries (ARL), 2023)
The Association of Research Libraries (ARL) is now accepting proposals for the 2024 Inclusion, Diversity, Equity, and Accessibility in Libraries & Archives (IDEAL) Conference, to be held July 15–17, in Toronto, Ontario, Canada. The conference theme is Sustainable Resistance and Restoration in Global Communities. Proposals should consider how the content of the session connects to the larger landscape of diversity, equity, inclusion, accessibility, and justice (DEIA/J) and how the session reasonably engages adult learners.
Worldwide
Keywords: 2023-08 August

The American Barbarossa Plan for Ukraine.1957 - Lurye, Oleg (The Times of Israel, 2023)
Exactly 66 years ago, in August 1957, the CIA released its secret report “Resistance Factors and Special Forces Areas. Ukraine.” This voluminous 200-page “work,” which resembled a doctoral dissertation, was prepared for the US intelligence community by staff members of Georgetown University. Despite its academic content, the CIA report is a detailed manual for the occupation of the Ukrainian territory by the Special Forces.
Ukraine
Keywords: 2023-07 July; Barbarossa Plan; CIA; Cold War; Georgetown University; United States of America

Justifying Extraterritorial Human Rights Obligations and Climate Change as a Counterexample - Raible, Lea (Blog of the European Journal of International Law: Talk!, 2023)
Extraterritorial human rights obligations are contentious. In the UK, for example, the ECtHR’s findings that armed forces deployed abroad have human rights obligations have met with criticism. Extraterritoriality is also routinely named as one of the most difficult aspects of the next generation of potentially groundbreaking human rights litigation: climate cases.
Worldwide
Keywords: 2023-07 July; Extraterritorial Application; Human Rights; International Law; Report

Conference - Why Isn’t Remembering Enough to Repair? - On line 2023-08-23 - Zócalo Public Square (Zócalo Public Square, 2023)
Upcoming events at Zócalo Public Square 2023-08-23: The Holocaust survivor Elie Wiesel did not believe in collective guilt. Instead, he asked for repair, and for holding the post-World War II generation of Germans responsible “not for the past, but for the way it remembers the past. And for what it does with the memory of the past.” Other societies and communities have taken up Wiesel’s call—at the national level, South Africa’s Truth and Reconciliation Commission and Argentina’s efforts to prosecute Dirty War military leaders, and at the local level, movements like the Greensboro Truth and Reconciliation Commission in North Carolina and land back efforts in the Pacific Northwest. What comes after we remember, from apology and forgiveness to reparations and justice?
United States of America
Keywords: 2023-07 July; Reparation

La caja de Pandora: Empresas de IA Generativa, ChatGPT y Derechos Humanos - Bacchiarelli, Anna; Aufiero, Paul (Humans Right Watch, 2023)
ChatGPT y la inteligencia artificial generativa (IA) dominan los titulares y las conversaciones. Pero, ¿qué hay detrás de esta tecnología? ¿Quién la alimenta de datos y decide de dónde proceden? ¿Qué tiene que ver con los derechos humanos?
Worldwide
Keywords: 2023-06 June

ICC Prosecutor Karim A.A. Khan KC announces launch of advanced evidence submission platform: OTPLink - ICC Office of the Prosecutor (International Criminal Court, 2023)
I am pleased to announce the launch of OTPLink, a new application for online and email-based evidence submissions by all external stakeholders and witnesses to my Office. OTPLink will provide a clear, single-access point, replacing various systems and processes that were previously in use for the receipt of information, including submissions pursuant to Article 15 of the Rome Statute.
Worldwide
Keywords: 2023-06 June